Method of generation of casual numbers on the basis of the use of apparatus of the computer plugged in the Internet - Чуприн, Володимир Михайлович; Вишняков, Володимир Михайлович; Пригара, Михайло Петрович (Ukrainian Information Security Research Journal, 2016)
In systems or voting poll on the Internet, with a view to ensuring the conditions for the free expression of respondents thought necessary secrecy of the vote. For this purpose cryptographic protection of information that needs to generate random numbers. It is known that the standard computer functions to generate random numbers, which are based on mathematical transformations, give a pseudorandom generator that resemble random, but random really. Knowing the methods of obtaining such numbers, hackers can crack the security system. In this paper makes recommendations on the principles of construction of computer programs generating real (not pseudo) casual numbers in the terminal nodes of the Internet, provided the exclusive use of standard software and hardware (without any additional physical devices). The experimental results of the proposed principles of random number generation. In theory, proved the impossibility of foreseeing the numbers received, indicating that the futility of trying to use cryptanalysis funds to disclose them